COASTAL RESOURCES CO-MANAGEMENT THROUGH LOCAL COMMUNITIY LIVELIHOOD IMPROVEMENT IN CU LAO CHAM ISLANDS, QUANG NAM - Trinh, Chu Manh (Vietnam Journal of Marine Science and Technology, 2008)
Coastal areas are facing with environmental and resources sustainable development. One of them is how livelihood improvement of the community who -living inside or around the coastal rosource areas. Especially, in locality where most of local people life depending strongly upon coastal environment and resources. The sharing rights - benefits between government and community (co-managmement) in reasonable utilisation and protection of coastal resources is consider as an useful tool for local level. Among, include aspects relating to local livelihood improvement. Based on studied results of livelihood improvement in high-quality fish sauce development in Cu Lao Cham islands, Quang Nam province, comanagement application in local level is primarily achieved in theory and also in practice. The paper presents the concepts of comanagement, livelihood and sustainable livelihood, as well as presents local livelihood proceed in case of high-quality fish sauce livelihood for Cu Lao Cham community which contribute to the coastal environment protection and resources reasonable utilisation in the marine protected area.